(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2021)
Compost can be used to reduce waste, it formed naturally, but it will take a long time, around 6-12 months. Bioactivators accelerate composting process; one of them is a solution of LMO (Local Microorganism) coconut pulp. The purpose of this study to determine the effectiveness of LMO coconut pulp for the composting time. The method in this research is quasi-experimental. This study consists of 3 treatments with 5 replications. Treatment 1 composting with the addition of LMO coconut pulp 50,000 ppm; treatment 2 composting with the addition of LMO coconut pulp 100,000 ppm; treatment 3 composting with the addition of LMO coconut pulp 200,000 ppm. The materials used in this study are vegetables and sawdust and the composting process carried out aerobically. From the observations, the average time to compile with LMO coconut pulp 50,000 ppm is 21.00 (21 days), 100,000 ppm 18.60 (19 days) and 200,000 ppm 18.20 (18 days). Based on the ANOVA test, the p value is 0.0001 (p <0.05) which means that H0 rejected, that there is a significant difference in composting time using LMO coconut pulp 50,000 ppm, 100,000 ppm, and 200,000 ppm. The most significant difference is between compost with LMO coconut pulp 50,000 ppm and compost with LMO coconut pulp 200,000 ppm. It is recommended for the further researchers using other types of waste, and test the quality of compost produced especially C/N compost. The community can use coconut pulp as a bioactivator in accelerating the composting process. Int. J. Agril. Res. Innov. Tech. 11(1): 109-116, June 2021